Synthesis, characterization and DNA binding studies of luminescent ruthenium(ii) imidazo complexes - Ting, Timothy Tze Chun (2014)
Ruthenium complexes have attracted as alternative drugs to cisplatin in cancer chemotherapy. Ruthenium polypyridyl complexes show lower toxicity than cisplatin and one of the application usages of ruthenium polypyridyl complexes with imidazole is in pharmaceutical chemistry. Long carbon chain length imidazoles have not been discussed in literature. Therefore, this study focuses on long carbon chain length imidazoles as ligands for ruthenium polypyridyl complexes and the studies with DNA. Four long carbon chain 2-(3,4-dialkoxy)-imidazo-[4,5- f][1,10]phenanthroline ligands were synthesized by condensation of [1,10]phenanthroline-5,6-dione and ammonium acetate first and then addition of 3,4-dialkoxybenzaldehydes into it. 1H NMR, mass spectrometry and FT-IR were used to identify the structure of 2-(3,4-dialkoxy)-imidazo-[4,5- f][1,10]phenanthroline. Three novel ruthenium(II) complexes, [Ru(II)(bpy)2L]2+where L = 1,10-phenanthroline derivatives of imidazole having 3,4- didecyloxy-phenyl (L10), 3,4-ditetradecyloxyphenyl (L14) and 3,4- dihexadecyloxyphenyl (L16) at position 2 were prepared by refluxing 2-(3,4- dialkoxy)-imidazo-[4,5-f][1,10]phenanthroline and Ru(bpy)2Cl2in a mixture of hot ethanol and water (7:3) for 24 hours under nitrogen which gives red complex. The previously reported ligand 3,4-dioctadecyloxyphenyl (L18) was also synthesized by reacting with Ru(bpy)2Cl2. All complexes were fully characterized by elemental analysis, 1H-NMR spectroscopy, ESI-MS and FT-IR. Their photophysical properties have also been studied by UV-visible spectroscopy and fluorescence spectroscopy. The complexes exhibit Ru(II) centered emissions at approximately 610 nm in acetonitrile solution at room temperature. In addition, the binding of these complexes to CT-DNA was studied using UV-Vis titration, luminescence titration and also viscosity measurements. The results showed that [Ru(bpy)2L10]2+ binds to CT-DNA by partial intercalation, while [Ru(bpy)2L14]2+, [Ru(bpy)2L16]2+and [Ru(bpy)2L18]2+were indicated to bind intercalatively via extended ligands. The affinities of the binding constants of these complexes were found to be in the order of 105- 106M-1.